Childhood Injury Prevention: Intervention in the Bedouin City of Rahat - Michal Hemmo-Lotem; Efrat Merrick; Liri Endy-Findling; Aziza Abu Freh; Claudia Jinich-Aronowitz; Liat Korn; Joav Merrick (The Scientific World Journal)
For several years, the National Center for Children's Health and Safety (Beterem) has worked on many levels to promote safety and prevent injury of the children in Israel. As part of intervention programs in 20 communities around Israel, this paper describes a 1-year, multidisciplinary, multistrategic childhood safety promotion and injury prevention project. The project took place in the Bedouin city of Rahat in the Southern part of Israel, the Negev, conducted by a local safety coordinator. This specific intervention study took place from March 2003 to March 2004. The main goal was to identify hazards and dangerous obstacles in public places in Rahat, then remove or repair the obstacles found, in order to secure a safe public environment for children. “Obstacle” was defined as any barrier that could endanger the safety of a child. Ten examples are used to illustrate this applied research project, and 80% of the problems were solved within the project period (time to solve between 1 week to 3 months, depending on various factors). We recommend the involvement of a safety coordinator from the community to focus on safety hazards for children, the use of a documentation diary to log the time frame, and also the use of pictures to illustrate the hazards and the changes, or to use as arguments in the lobbying process.